A SIMULATION BASED SCHEDULING IN BUS RAPID TRANSIT SYSTEM - Pekel, Engin; Kara, Selin Soner (YILDIZ TECHNICAL UNIV, 2015)
Population density difference between regions has continued to increase sharply. It has happened with the impact of factors such as Industry, suitable climatic conditions, tourism and transportation and the public transport has become more mixed. It is clear that this mixed theme should be boosted for both ones who service and ones who get service, if this recovery was happened with a stochastic schedule based on simulation, it will make the system more optimal. Having carried out the system to be modeled by using Arena simulation software in the scope of this study, the system will be analyzed with diverse scenarios. However, it is required some data such as inter-arrival times of passengers, inter-stops times, capacity of bus in order to run the model and statistical distributions of some of them will be determined. With the success of an optimal scheduling, it's aimed to meet the required capacity for the passengers who received service in the Metrobus line.
Keywords: Bus rapid transit; simulation; modeling; scheduling; public transport; Engineering